Pilot-scale sorption studies of diethylketone in the presence of Cd2+ and Ni2 - Costa, Filomena (Environmental technology, 2019)
The effect of pH on the sorption capacity of vermiculite towards cadmium and nickel was tested in batch systems and it was shown that the sorption percentages increase with an increase in the mass of vermiculite and with an increase in the initial pH. Maximum sorption percentages were obtained for a pH of 8 and 4 g of vermiculite (86.5% for Cd2+ and 86.1% for Ni2+, for solutions with 100 mg/L of metal). As a consequence, it was possible to establish a range of optimal pH for biosorption processes, by combining the so determined optimal sorption pH of vermiculite with the optimal growth pH of Streptococcus equisimilis, a bacterium used to treat contaminated water. Pilot-scale experiments with a S. equisimilis biofilm supported on vermiculite were conducted in closed-loop conditions, aiming to treat large volumes of diethylketone aqueous solutions, eventually containing Cd2+ or Ni2+. The excellent capacity of this joint system to simultaneously biodegrade diethylketone and biosorb Cd2+ or Ni2+was proved. The removal percentage and the uptake increase through time, even with the replacement of the initial solution by new ones. The breakthrough curves that best describe the results achieved for Cd2+ and Ni2+ are respectively the Adams-Bohart and the Yoon and Nelson model